Do clinical decision support systems for prescribing improve patient safety? a systematic literature review - Sri Kusumadewi; Isnatin Miladiyah (Institute of Advanced Engineering and Science, 2023)
Clinical decision support systems (CDSS) are developed independently or connected to the electronic health record (EHR) or other computerized systems. The study begins with identification by searching the literature through the Google Scholar, PubMed and ScienceDirect databases. The search results obtained 5,595 articles. Forty-two articles were obtained, which were used further. Most of the research focus is on